Armor and Anesthesia: Exposure, Feeling, and the Soldier’s Body - MacLeish, Kenneth T. (2012)
For many civilians, the high-tech weapons, armor, and military medicine with which U.S. soldiers are equipped present an image of lethal capacity and physical invulnerability. But, as this article explores, soldiers themselves just as often associate the life-sustaining technology of modern warfare with feelings that range from a pragmatic ambivalence about exposure to harm all the way to profoundly unsettling vulnerability. This article, based on fieldwork among soldiers and military families at the U.S. Army’s Ft. Hood, examines sensory and affective dimensions of soldiers’ intimate bodily relationships with the technologies that alternately or even simultaneously keep them alive and expose them to harm. I argue that modern military discipline and technology conspire to cultivate soldiers as highly durable, capable, unfeeling, interchangeable bodies, or what might be called, after Susan Buck-Morss (1992), anesthetic subjects. But for soldiers themselves, their training, combat environment, protective gear, and weapons are a rich font of both emotional and bodily feeling that exists in complex tension with the also deeply felt military imperative to carry on in the face of extreme discomfort and danger.